444 nm InGaN light emitting diodes on low-defect-density GaN templates on patterned sapphire. (14th September 2017) - Khoury, Michel; Li, Hongjian; Kuritzky, Leah Y.; Mughal, Asad J.; DeMierry, Philippe; Nakamura, Shuji; Speck, James S.; DenBaars, Steven P.
Abstract: Efficient InGaN-based 444 nm blue light-emitting diodes (LEDs) were fabricated on low-defect-density semipolar GaN templates grown on patterned r-sapphire. At 20 A/cm 2, the packaged LEDs exhibited a light output power of 2.9 mW (17.8 mW at 100 A/cm 2 ) and a record peak external quantum efficiency of 6.4% showing a negligible efficiency droop and blue shift with drive currents up to 100 A/cm 2 . In addition, we demonstrated light extraction simulations for the template, which showed that the structured pattern is not only beneficial for limiting the defect propagation but also increases the light extraction by 29% compared with GaN layers grown on planar substrates.